Effect of motivation of employee, safety and health on employee performance - Yoyok Soesatyo, P. Priyono, Sunda Ariana, Lucky Cadalora Putra, (Opción, 2019)
This study aims to examine (1) the effect of work motivation on performance (2) the effect of occupational safety on performance (3) the effect of occupational health on performance (4) to test which of the work motivation, occupational safety and occupational health.The sample in this research is 115 employees, while the analysis conducted by using Multiple Linear Regression.The results of the test are(a) Environmental conditions significantly affect job performance (b) Motivation has a significant effect on performance(c) The motivation holds a mediating effect between the relationship between working conditions and work performance.